Characterization of Rural Tourism Marketing to Strengthen Skills in Indigenous Communities of Chimborazo, Ecuador - GUERRERO VACA, Daniel Marcelo; CEJAS MARTÍNEZ, Magda Francisca; PACHECO SANUNGA, Héctor Germán; GARCÍA MEYTHELER, Carlos Eduardo; PROAÑO LUCERO, Gabriela Elizabeth (Journal of Environmental Management and Tourism; Vol 13 No 4 (2022): JEMT, Volume XIII, Issue 4(60), Summer 2022DO - 10.14505/jemt.v13.4(60).26, 2022)
The sustainability of tourism management in indigenous communities that adopt tourism as a way of life is an issue that contributes to local and national development. The general objective of the study was to characterise tourism marketing in order to dynamise and strengthen the competencies of indigenous communities in the province of Chimborazo in Ecuador, and it was a descriptive-explanatory field study. As a result, evidence was obtained of the absence of marketing principles, strategies and tools to generate impact results in rural tourism service providers and, consequently, in the province and its cantons. It is concluded that the characterisation can, through educational interventions in communities, and accompaniment until the final implementation, incorporate these principles for social, community and tourism benefit.